The critical roles and therapeutic implications of tuft cells in cancer - Li, Lin; Ma, Mengmeng; Duan, Ting; Sui, Xinbing (Frontiers in Pharmacology, 2022)
Tuft cells are solitary chemosensory epithelial cells with microvilli at the top, which are found in hollow organs such as gastrointestinal tract, pancreas, and lung. Recently, increasing study has revealed the chemotactic abilities and immune function of the tuft cells, and numerous efforts have been devoted to uncovering the role of the tuft cells in tumors. Of note, accumulating evidence has shown that the specific genes (POU2F3, DCLK1) expressed by the tuft cells are involved in vital processes in carcinogenesis and cancer development. However, the interaction between the tuft cells and cancer remains not fully explained. Therefore, we concluded the functional roles and potential therapeutic implications of the tuft cells in cancers, including pancreatic cancer, lung cancer, gastric cancer, colon cancer, and liver cancer, based on biological processes and specific markers of the tuft cells, which will inspire the future research of the tuft cells in novel strategies for cancer therapies.